CHEMICAL CONTROL EVALUATION OF ALEXANDER GRASS (Brachiaria plantaginea) ON MAIZE (Zea mays) YIELD - Galon, Leandro (2010)
The objective of this study was to evaluate the Brachiaria plantaginea control with pre and post-emergence herbicides and their effects on the hybrid Pioneer 3063 maize yield. The trial was conducted by using a complete randomized blocks design, with four replications, under the conventional sowing system. The treatments consisted of the herbicide s-metolachlor (1,620 g ha-1) and the mixture in tank of atrazine + nicosulfuron (1,250 + 28 g ha-1), applied in pre and early post-emergence of the culture, respectively, plus one infested and one weed-free control. The plants of B. plantaginea were obtained from the soil seed bank, with average population of 312 plants m-2. The evaluated variables were control of B. plantaginea by the herbicides and maize grain yield components, as well as grain yield. Among the herbicides, the one that provided better control of B. plantaginea was the mixture atrazine plus nicosulfuron, applied in post-emergence of the crop, maintaining the field free of B. plantaginea, from the beginning to the end of the cycle. The herbicide s-metolachlor showed to be an alternative for the initial control of weeds in maize, up to 20 days after emergence. The absence of B. plantaginea control causes interference in all grain yield components of maize, being observed up to 98% of grain yield losses. KEY-WORDS: Chemical control; herbicide mixtures; weed.